2002
DOI: 10.1046/j.1360-0443.2002.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying extinction research and theory to cue‐exposure addiction treatments

Abstract: Given what is known from animal extinction theory and research about extinguishing learned behavior, it is not surprising that cue-exposure treatments so often fail. This paper reviews current animal research regarding the most salient threats to the development and maintenance of extinction, and suggests several major procedures for increasing the efficacy of cue-exposure addiction treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
594
0
17

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 641 publications
(635 citation statements)
references
References 57 publications
24
594
0
17
Order By: Relevance
“…Here it was shown that merely presenting the interoceptive drug-S D alone in a standard method of Pavlovian extinction (i.e., cue exposure) may not be sufficient to minimize food-seeking behavior-"relapse" (cf. Conklin & Tiffany, 2002;Tiffany, 2009)-but this may likely vary as a function of the stimulus nature of the cue(s) and where such cues undergo extinction in relation to the primary reinforcer.…”
Section: Discussionmentioning
confidence: 99%
“…Here it was shown that merely presenting the interoceptive drug-S D alone in a standard method of Pavlovian extinction (i.e., cue exposure) may not be sufficient to minimize food-seeking behavior-"relapse" (cf. Conklin & Tiffany, 2002;Tiffany, 2009)-but this may likely vary as a function of the stimulus nature of the cue(s) and where such cues undergo extinction in relation to the primary reinforcer.…”
Section: Discussionmentioning
confidence: 99%
“…The technique proved to be useful in evaluating the S-O-R account of PIT; but it could also have clinical relevance. Pavlovian cues influence our behaviour in many ways -such as the role of Pavlovian cues associated with drugs in craving and relapse (Conklin & Tiffany, 2002;LeBlanc, Ostlund & Maidment, 2012). The fact that specific PIT seems insensitive to outcome devaluation (Holland, 2004) and S-O extinction (Delamater, 1996) presents a challenge for therapy.…”
Section: Figure 6 About Herementioning
confidence: 99%
“…39-48, Ainslie, 2001, and conditioning is unnecessary to account for sudden craving, as we will now argue. It is interesting also, but only suggestive, that etiologies based on conditioning promise treatments using extinction or counterconditioning, but attempts to extinguish conditioned responses have been shown in a recent meta-analysis to be useless in recovery from addiction (Conklin and Tiffany, 2002).…”
Section: Can Conditioning Do the Job?mentioning
confidence: 99%